Codelivery of dual drugs from polymeric micelles for simultaneous targeting of both cancer cells and cancer stem cells. (September 2015) - Krishnamurthy, Sangeetha; Ng, Victor WL; Gao, Shujun; Tan, Min-Han; Hedrick, James L; Yang, Yi Yan
Aim: Phenformin-loaded micelles (Phen M) were used in combination with gemcitabine-loaded micelles (Gem M) to study their combined effect against H460 human lung cancer cells and cancer stem cells (CSCs) in vitro and in vivo .Materials & methods: Gem M and Phen M were prepared via self-assembly of a mixture of a diblock copolymer of PEG and urea-functionalized polycarbonate (PEG-PUC) and a diblock copolymer of PEG and acid-functionalized polycarbonate (PEG-PAC) through hydrogen bonding and ionic interactions. Gem M and Phen M were characterized and tested for efficacy both in vitro and in vivo against cancer cells and CSCs.Results: The combination of Gem M/Phen M exhibited higher cytotoxicity against CSCs and non-CSCs than Gem M and Phen M alone, and showed significant cell cycle growth arrest in vitro . The combination therapy had superior tumor suppression and apoptosis in vivo without inducing toxicity to liver and kidney.Conclusion: The combination of Gem M and Phen M may be potentially used in lung cancer therapy.